Clinical evaluation of the 14C fat absorption test. Issue 2 (February 1974) - Burrows, P. J.; Fleming, J. S.; Garnett, E. S.; Ackery, D. M,; Colin-Jones, D. G.; Bamforth, J.
Abstract : The absorption of 14 C-labelled glyceryl tripalmitate was tested in 62 patients by determining the maximum specific activity of CO2 in the breath after an oral dose. A significant correlation with faecal fat excretion was found. The absorption of 14 C labelled palmitic acid was tested subsequently in 54 patients. In cases of pancreatic steatorrhoea, normal absorption of palmitic acid with impaired absorption of glyceryl tripalmitate was found, whereas in most patients with coeliac disease the absorption of both substances was depressed to the same extent.